Strategi Pembelajaran Kontekstual untuk Meningkatkan Pemahaman Konsep Siswa Sekolah Dasar - Aura Yolanda; Masnur Sihotang; Joner Alfin Zebua; Mita Hutasoit; Yeni Lupitasari Sinaga (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
Contextual learning is an approach that links subject matter to real world situations experienced by students. This approach aims to improve students' conceptual understanding and critical thinking skills. This article discusses the implementation of contextual learning strategies in elementary schools and their impact on students' conceptual understanding. Through this method, students are invited to connect the knowledge gained with everyday life thereby increasing their learning motivation and understanding.